Septostomía atrial percutánea con balón en el tratamiento de la insuficiencia cardíaca - Rodríguez Blanco, Suilbert; Aguilar Medina, José M.; Leyva Quert, Abel Y.; Prohías Martínez, Juan A. (CorSalud, 2021)
Septostomía atrial percutánea con balón en el tratamiento de la insuficiencia cardíaca